POWER SPECTRUM FEATURES OF THE NEAR-EARTH ATMOSPHERIC ELECTRIC FIELD IN KAMCHATKA - Mikhailov Y.M.; Mikhailova G.A.; Kapustina O.V.; Buzevich A.V.; Smirnov S.E. (My University, 2004)
Power spectrum of the diurnal variations of the quasi-electrostatic field Ez in the near-Earth atmosphere have been presented for the first time. The Ez power spectrum variations in the period of fine weather have been shown to exhibit two bands of the periods of natural atmospheric oscillations with T = 1-5 and 6-24 h. These oscillations are the modes of the internal gravity and tidal waves in the lower atmosphere. On the days under atmospheric precipitation, the spectral power of Ez increases by an order of magnitude. During the pre-earthquake period, when the diurnal Ez variation had an anomaly, the intensity of harmonics with T = 1.8, 2.2, and 3.8 h increased by an order of magnitude or more in comparison with the Ez spectra in fine weather. Two additional spectral bands with T = 0.6 and 1 h have appeared simultaneously.